Eyewitness Auschwitz : three years in the gas chambers - Muller, Filip; Freitag, Helmut; Flatauer, Susanne; Muller, Filip (Chicago Ivan R. Dee, 1999)
Filip Muller's firsthand account of three years in the gas chambers. One of the few prisoners who saw the Jewish people die and lived to tell about it, Muller has written one of the key documents of the Holocaust. A very detailed description of day-to-day life, if we can call it that, in Hell's inmost circle ... jammed with infernal information too terrible to be taken all at once.
No return -- Into the crematorium -- The new death factories -- The tragedy of the Family Camp -- The inferno -- Plans of Auschwitz.
Keywords: Muller, Filip; Auschwitz (Concentration camp); World War -- 1939-1945; Prisoners of war -- Czechoslovakia; Prisoners of war -- Poland; Tweede Wereldoorlog; Concentratiekampen; Czechoslovakia; Poland; Auschwitz; Biography; Personal narratives